2022
DOI: 10.3390/ijerph19074057
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Impact of Scientific Reports Published by EFSA and GIS on Functional Foods Newly Placed on the Market in Poland

Abstract: Dietary supplements are health-promoting products. The legal categorization of dietary supplements as foods does not raise concerns, but a general understanding of how they work in the human body seems to deviate from the official definition. Thus, it is necessary to establish effective methods of market control related to dietary supplements. This research aims at assessing the impact of recommendations by various food safety authorities on ingredients used in newly registered products. It probes how the prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Monitoring of the use of supplements seems to be particularly important in those countries where no authorisation procedures are required before the product is placed on the market [44]. In most European Union countries, notification systems for dietary supplements are in place, but only a few include authorisation procedures based on quality assessment before product release [36]. Following the example of France, some EU countries implemented their own, national dietary supplements adverse effects reporting systems [45], However, many still have no procedures for monitoring or collecting dietary supplements' adverse reactions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Monitoring of the use of supplements seems to be particularly important in those countries where no authorisation procedures are required before the product is placed on the market [44]. In most European Union countries, notification systems for dietary supplements are in place, but only a few include authorisation procedures based on quality assessment before product release [36]. Following the example of France, some EU countries implemented their own, national dietary supplements adverse effects reporting systems [45], However, many still have no procedures for monitoring or collecting dietary supplements' adverse reactions.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, in Poland and France, companies placing dietary supplements on the market should notify the local food safety authority [36], while in the USA, a notification procedure is not established for regular products [24]. Regardless of this difference, it should be noted that in all countries of which ADEs reporting systems were included in this study, food companies do not need to obtain authorisation for dietary supplement marketing.…”
Section: Introductionmentioning
confidence: 95%
“…It may mean that, regardless of the simple and cost-free procedure of notification, entrepreneurs fail to comply with the duty of submitting the notification of trading in dietary supplements. Such a hypothesis is backed up by the presence of a large number of submissions in the RASFF relevant to the presence of yohimbine, regardless of a noticeable fall in notification submissions for products containing it observed since the beginning of 2019 [11]. Under the RASFF, it was also found that there are typically medicinal substances that cannot be entered into a notification form.…”
Section: Discussionmentioning
confidence: 99%
“…Our earlier research led to the conclusion that the national register of functional foods, such as the RASFF, may be a valuable source of information in the process of the selfregulation of the market of dietary supplements in Poland; nevertheless, further research in relation to particular ingredients is worth undertaking. An analysis in that direction may help to identify dishonest market practices resorted to by the producers and distributors of non-conforming products [11]. This is of particular significance as we are observing an increase in dishonest market practices, the purpose of which is to generate more profits from the sale of fraudulent dietary supplements or misleadingly advertised [12] while their effective detection causes many difficulties, caused, among others, by lack of data on newly launched products on the market [13].…”
Section: Introductionmentioning
confidence: 99%